Pengaruh Penerapan Model Kooperatif TGT Terhadap Hasil Belajar Siswa Mata Pelajaran IPS - Rizky, Adiva Apriliani; Shinta Oktafiana (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The learning model is an important factor influencing student learning outcomes. The low achievement of students in social studies at SMPN 4 Pamekasan is still a problem, mainly due to the use of less innovative models such as the lecture method, which limits active participation. This study aims to examine three key aspects. First, to analyze the effect of the TGT learning model on the learning outcomes of eighth-grade students at SMPN 4 Pamekasan and to what extent the TGT model can improve student performance. Second, to compare the average pretest and posttest scores of students using the TGT model. Third, to compare the same scores for students taught using conventional methods. This research uses a quantitative approach with a quasi-experimental method and a Pretest-Posttest Nonequivalent Control Group design. Pretests and posttests were conducted in both groups. The results showed a significance value of 0.014 with a t-count of 6.619, indicating a significant effect of the TGT model. N-Gain analysis showed a 90% increase in the experimental group and 26% in the control group. The experimental class improved from 32.19 to 92.76, while the control class increased from 43.64 to 60.00, proving the greater effectiveness of the TGT model.